2014
DOI: 10.4141/cjps2013-294
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seed size, seed treatment, seeding date and depth on Rhizoctonia seedling blight of canola

Abstract: 2014. The effect of seed size, seed treatment, seeding date and depth on Rhizoctonia seedling blight of canola. Can. J. Plant Sci. 94: 311Á321. Rhizoctonia solani can have a substantial impact on seedling establishment and productivity of canola (Brassica napus). The effects of seeding date, seeding depth, seed size, and seed treatment on seedling blight of canola were evaluated under greenhouse and field conditions. Early seeding resulted in higher seedling emergence in one trial year and higher seed yield in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…R. solani AG2-1 is most aggressive to young seedlings and host resistance to infection increases with age ( Verma, 1996 ). Therefore faster developing OSR cultivars are more likely to escape the disease and traits related to early germination and establishment, such as seed size will be important for breeding new varieties that are more likely to tolerate R. solani infection ( Hwang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…R. solani AG2-1 is most aggressive to young seedlings and host resistance to infection increases with age ( Verma, 1996 ). Therefore faster developing OSR cultivars are more likely to escape the disease and traits related to early germination and establishment, such as seed size will be important for breeding new varieties that are more likely to tolerate R. solani infection ( Hwang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Canola seed size effects on crop emergence and yield have been inconsistent. Under greenhouse conditions, Hwang et al (2014) showed that midsize seed (0.7 to 2.0 mm) had a higher emergence rate than smaller or larger seed, but that larger seed led to greater shoot weight and plant height. Under field conditions, the same authors found no seed size effect on canola emergence, but at one of two very low-yielding sites inoculated with Rhizoctonia solani, midsize seed (0.7 to 2.0 mm) yielded greater than smaller or larger seed.…”
mentioning
confidence: 97%
“…R. solani has been shown to cause severe damping off in Brassica crops in Finland (Linnasalmi, ; Tahvonen et al , ) but formation of stem symptoms in older OSR plants has not been studied before. R. solani , predominantly AG 2–1, has been shown to be the major cause of post‐ and pre‐emergence damping off of OSR crops worldwide (Berkenkamp & Vaartnou, , Gugel et al , ; Kataria & Verma, ; Verma, ; Khangura et al , ; Hwang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A late sowing date in our study increased considerably the risk of high stem lesion incidence, while an effect of sowing date on root rot risk was less evident. The effect of sowing date on Rhizoctonia attack is dependent on soil temperature, soil moisture and the predominant R. solani anastamosis group present in the field and therefore results on the effect of sowing date are variable in different studies and sometimes conflicting (Hwang et al , ). In Canadian studies, the high incidence of Rhizoctonia seedling blight is often connected to early sowing when the soil is relatively cool and wet and AG 2–1 is predominant (Yitbarek et al , ; Kataria & Verma, ; Verma, ), whereas attack by AG 4 isolates later in the season is favoured by warm temperatures (Teo et al , ; Verma, ).…”
Section: Discussionmentioning
confidence: 99%